Offshore wind farms in Greece - Vardaka Athina Danai; Fantidis Jacob G.; Karakoulidis Konstantinos G. (E3S Web of Conferences)
Focusing on recent legislative developments, the licensing system, and the fundamental timeline for project development, this survey offers an overview of the present regulatory framework guiding the development of offshore wind farms in Greece. With regards to the demands of alternative energy provisions, Greece’s spatial planning for renewable energy sources, urgently needs to be updated. Therefore, the required standards may become more detailed as a result of the maritime spatial frameworks that will be established at the regional level. This activity will be addressed through a maritime spatial planning system (e.g., a Special Maritime Spatial Plan for RES). is not available in Greece. It is anticipated that the upgrading of the spatial framework will provide the required environmental standards on a strategic level, as well as the public interest and legal clarity for potential investors. In this work eight different Greek islands are chosen as case studies in order to evaluate the energy production from wind.